Exploring Factors Affecting High-School Student Entrepreneurship Competency - Nirinpat Angmani; Aukkapong Sukkamart; Paitoon Pimdee; Akan Narabin; Akkarin Thongkaw (International Journal of Instruction, 2024)
Entrepreneurial competencies are increasingly recognized as essential skills for students in today's dynamic and competitive world. This study aims to identify and validate the crucial entrepreneurial competencies of Thai high school students using a 2nd-order confirmatory factor analysis (CFA). A questionnaire was developed to assess these competencies, administered to a sample of high school technology teachers selected using multi-stage random sampling. The results indicated that technology teachers perceive the development of entrepreneurial competencies as crucial for their students. Specifically, the analysis revealed that entrepreneurial skills, leadership skills, and innovative adaptability were most important. These findings suggest that enhancing these competencies can significantly contribute to students' overall entrepreneurial potential. The research contributes to the understanding of entrepreneurial competencies among high school students and provides a validated framework for assessing these competencies. The study's novelty lies in its validation of essential entrepreneurial competencies specifically tailored for Thai high school students, offering a framework for assessing and nurturing these competencies in an educational context.
Keywords: Entrepreneurship Studies and Influences